(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article explores the significance of standardized student assessment in modern education. As educational systems move towards competency-based frameworks, the need for clear, transparent, and fair assessment standards becomes essential. Effective assessment not only measures student achievement but also motivates learning and supports personal growth